Disruption of the moonlighting function of CTF18 in a patient with T-lymphopenia - Robert Sertori; Billy Truong; Manoj K. Singh; Susan Shinton; Rachael Price; Andrew Sharo; Paulameena Shultes; Uma Sunderam; Sadhna Rana; Rajgopal Srinivasan; Sutapa Datta; Joan Font-Burgada; et al. (Frontiers in Immunology)
IntroductionNewborn screening for immunodeficiency has led to the identification of numerous cases for which the causal etiology is unknown.MethodsHere we report the diagnosis of T lymphopenia of unknown etiology in a male proband. Whole exome sequencing (WES) was employed to nominate candidate variants, which were then analyzed functionally in zebrafish and in mice bearing orthologous mutations.ResultsWES revealed missense mutations in CHTF18 that were inherited in an autosomal recessive manner. CTF18, encoded by the CHTF18 gene, is a component of a secondary clamp loader, which is primarily thought to function by promoting DNA replication. We determined that the patient’s variants in CHTF18 (CTF18 R751W and E851Q) were damaging to function and severely attenuated the capacity of CTF18 to support hematopoiesis and lymphoid development, strongly suggesting that they were responsible for his T lymphopenia; however, the function of CTF18 appeared to be unrelated to its role as a clamp loader. DNA-damage, expected when replication is impaired, was not evident by expression profiling in murine Chtf18 mutant hematopoietic stem and progenitor cells (HSPC), nor was development of Ctf18-deficient progenitors rescued by p53 loss. Instead, we observed an expression signature suggesting disruption of HSPC positioning and migration. Indeed, the positioning of HSPC in ctf18 morphant zebrafish embryos was perturbed, suggesting that HSPC function was impaired through disrupted positioning in hematopoietic organs.DiscussionAccordingly, we propose that T lymphopenia in our patient resulted from disturbed cell-cell contacts and migration of HSPC, caused by a non-canonical function of CHTF18 in regulating gene expression.